Depression symptoms and quality of life in patients receiving renal replacement therapy in Jordan: A cross-sectional study. (June 2021) - Muflih, Suhaib; Alzoubi, Karem H.; Al-Azzam, Sayer; Al-Husein, Belal
Abstract: Patients with chronic illnesses, such as those with chronic kidney disease (CKD) that are undergoing renal replacement therapy (RRT), face significant psychological changes. This descriptive cross-sectional research was carried out to investigate the factors that influence depressive symptoms and quality of life (QoL) in patients with end-stage renal disease. Data were collected from 70 participants undergoing RRT using a self-reported questionnaire that included sociodemographic information, depressive symptoms, disease status, and QoL. The Beck Depression Inventory-II (BDI-II) screening scale was used to measure depressive symptoms and the SF-36 (Medical Outcome Survey-Short Form 36) was used to assess QoL. Participants in the study rated their depressive symptoms as 'minimum (44.3%), 'mild' (20%), 'moderate' (21.4%), and 'severe (14.3%). Furthermore, a shorter duration of dialysis and comorbid conditions were significantly associated with the development of depressive symptoms. Patients on RRT for a longer period of time had lower physical activity scores than patients on dialysis for a shorter period of time. Male participants have a higher mental QoL than female participants, suggesting that the mental aspect of renal disease is less impaired than the physical aspect. The findings of this study are expected to increase awareness of RRT therapy targets and enhance patient outcomes. Highlights: Patients who received dialysis for longer-duration reported less depression symptoms. There were no strong correlations between depression severity and age or gender. Patients who received RRT for a longer time had lower levels of physical activity. Moderate to severe depressive symptoms had an effect on mental health and vitality.